PRODUCCIÓN DE PLANTA CLONAL DE QUERcus ILEX L. MEDIANTE EMBRIOGÉNESIS SOMÁTICA PARA MICORRIZACIÓN CON TUBER MELANOSPORUM Vitt. - Mauri, P V; Garcia, G; Fernandez-Galiano, E (II Congreso Forestal Español, 1997)
Quercus ilex L. is the most important tree for the micorritation with Tuber melanosporum Vitt. Quercus ilex L. acorns were collected during the summer and they were surface sterilized with a 15% NaC10H solution. Zygotic embryos were then plated in darlrness during 30 days in a MS medium containing PRL-4-C macrosalts. Different concentrations of growth regulators (NAA, BA and 2,4D) were added to the basic medium for inducting somatic embryogenesis. Explants were transferred to a basal medium supplemented with 0,5 MBA and 0,5 MNAA, during 30 days in light. The somatic embryogenesis response appeared in every media assayed, even in the one with no PGRs, except in those containing 3. M 2,4D. The somatic embryos appeared from embryogenic yellow, friable callus or directly from the apical axis. Once the embryonic callus was transferred to PGRs free medium, secondary embryogenesis appeared repetitively. Somatic embryogenesis in Quercus ilex L. seems not to dependent on the PGRs added, appearing even with no PGRs. Secondary embryogenesis allows a continuing production of somatic embryos, essential to obtain high amounts of clonal plants.
Keywords: Plant Growth Regulators; Quercus ilex L.; secondary embryogenesis; Somatic embryogenesis; Tuber melanosporum Vitt.; zygotic embryos